2014
DOI: 10.1177/155892501400900113
|View full text |Cite
|
Sign up to set email alerts
|

Photochromic and Thermochromic Colorants in Textile Applications

Abstract: Commercial photochromic and thermochromic colorants that change rapidly and reversibly from colorless to colored state when activated by stimuli like ultraviolet irradiation, temperature or pH are well established class of colorants for manufacturing of niche products. Use of photochromic and thermochromic systems in applications like medical thermography, plastic strip thermometers, photochromic lenses, food packaging and nondestructive testing of engineered articles and electronic circuitry is well documente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
76
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 33 publications
0
76
0
3
Order By: Relevance
“…The reaction is reversible, meaning that after removal of the illuminator, the photochromic dye reverts to its original (colourless) form. Photochromic dyes are applicable in a variety of areas, such as ophthalmics, information‐recording materials, dye laser and textile industry . Among these, ophthalmics represents the majority of consumed photochromic dyes, whilst the other above‐mentioned areas only represent a few per cent of the total value of the global business sales.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction is reversible, meaning that after removal of the illuminator, the photochromic dye reverts to its original (colourless) form. Photochromic dyes are applicable in a variety of areas, such as ophthalmics, information‐recording materials, dye laser and textile industry . Among these, ophthalmics represents the majority of consumed photochromic dyes, whilst the other above‐mentioned areas only represent a few per cent of the total value of the global business sales.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, ophthalmics represents the majority of consumed photochromic dyes, whilst the other above‐mentioned areas only represent a few per cent of the total value of the global business sales. In textiles, photochromic dyes can be found in products with special colour effects (T‐shirts, handbags and caps), textured yarns for knitting, weaving and embroidery, UV‐light‐sensitive curtains and special photochromatic fabrics . Photochromic dyes can be applied on textiles using printing , exhaust dyeing , and pad dyeing .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the wash fastness of such thermochromic systems needs to be improved further, as it may not match the stringent demands of modern‐day consumers. Another important aspect would be to improve the light fastness of the thermochromic pigments used in this study, as it was not found to be satisfactory .…”
Section: Resultsmentioning
confidence: 99%
“…Thermochromic materials are intriguing substances, which exhibit reversibly color change depending on change of temperature . Because of their temperature sensing property, thermochromic materials have attracted considerable interest and are tested to determine their potential in many products and application areas like thermal indicators, optical storage devices, other luminescent switches, building coatings and cement, security printing plastic strip thermometers, food packaging, medical thermography, nondestructive testing of engineered articles, electronic circuitry, and pharmaceutical industry . Recently, textile industry has become one of the most interested sectors to thermochromic materials.…”
Section: Introductionmentioning
confidence: 99%